Virus H1N1 Neuraminidase Secara Sederhana Dengan Pendekatan In-Silico: Neuraminidase H1N1 Virus Vaccine Design In A Simplified In-Silico Approach - Elfrida Roulina Simanjuntak; Toepak, Erwin Prasetya (Jurnal Jejaring Matematika dan Sains, 2021)
In Indonesia in 2019 a case of H1N1 infection was reported in North Sumatra. This virus is a single stranded-ribonucleid acid (ss-RNA) virus with a diameter of 80-120 nm and a length of 200-300 nm, has an envelope with a lipid bilayer and is surrounded by about 500 glycoprotein spikes that have hemagglutination (HA) and neuraminidase (NA) enzymes. ). Neuraminidase is an enzyme whose job is to carry out atixialolytic enzyme activity, releasing viral progeny trapped on the surface of infected cells when they are released and facilitating the movement of the virus in the mucous membrane of the target epithelial tissue. attachment of viruses to targets of interest to antiviral drugs. The in-silico method is one of the research studies in a computational-based biology. This method of analysis is used to identify a chemical property in a chemical compound. In the extraction of neuraminidase H1N1 protein sequences (swine virus) from NCBI, there were 469 AA proteins obtained in-silico. The antigenity test using a web vaccine on the NA protein of the H1N1 virus, with a holding value of 0.4 which is the final result of protein residues, indicates that the overall probability is estimated to be antigen with 0.4982.